Enhanced three - dimensional planning and modelling techniques for craniofacial reconstruction surgery [compact disc] - 395842 Muhammad Azam Rana; Halim Setan, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Doktor Falsafah (Geoinformatik)) - Universiti Teknologi Malaysia, 2007